CONSIDERATIONS FROM HISTORY: APPLYING THE THEORIES OF GLUBB AND IBN KHALDUN TO MODERN EMPIRES - Houti, Abdelqadir; Idriz, Mesut; Okleh, Issam (Al-Adab Journal, 2025)
This paper explores the application of historical theories by Sir John Glubb and Ibn Khaldun to analyze modern empires, specifically the United States and China. Glubb's six stages of empires and Ibn Khaldun's concept of Asabiyyah provide valuable frameworks for understanding the dynamics of empire-building and decline. The paper examines key factors such as leadership, social cohesion, economic growth, and moral integrity in sustaining the power of modern states. By comparing Glubb's "Age of Decadence" and Ibn Khaldun's theories of social fragmentation, this research identifies the importance of strong, ethical leadership and unity in preventing the decline of empires. The paper also emphasizes the need for economic and political reforms to ensure a balanced distribution of wealth and maintain prosperity. Through the lens of historical analysis, the paper highlights the relevance of these theories for understanding the challenges faced by contemporary powers. It offers insights into strategies that can help maintain the vitality and resilience of modern empires. Ultimately, it underscores the value of historical lessons in shaping future trajectories of global powers.